Diagnosis of catheter-related infections - Geiss, Heinrich K. (Zentralblatt für Bakteriologie, 1995)
Catheter-related infections (CRI) are a major cause of febrile episodes in hospitalized patients. Additionally, approximately 40% of primary infections in intensive care patients are directly related to central venous catheters. Despite the clinical significance of CRI diagnostic procedures are still under debate. Clinical diagnosis which includes systemic signs of infection and suppuration at the catheter entry site is altogether a rare event. Therefore, most cases are still diagnosed by laboratory methods. Although the semiquantitative roll-plate technique is widely used and frequently regarded as gold standard, the disadvantages of a post-hoc diagnosis are obvious. In-situ techniques which leave the suspected catheter in place include differential blood cultures, skin and hub cultures and a new method of microscopic screening of blood drawn through the inflicted catheter. However, until now the true value of all these methods still lack unanimous acceptance. Further research is necessary to close the gap between clinical expectations and laboratory results.
Elektronische Reproduktion der Druck-Ausgabe 8. November 2011
Gesehen am 12.03.2025